2011
DOI: 10.1093/biostatistics/kxr021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating prognostic accuracy of biomarkers in nested case-control studies

Abstract: Nested case-control (NCC) design is used frequently in epidemiological studies as a cost-effective subcohort sampling strategy to conduct biomarker research. Sampling strategy, on the other hoand, creates challenges for data analysis because of outcome-dependent missingness in biomarker measurements. In this paper, we propose inverse probability weighted (IPW) methods for making inference about the prognostic accuracy of a novel biomarker for predicting future events with data from NCC studies. The consistency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 28 publications
0
82
0
Order By: Relevance
“…A nested case-control study can be viewed as a cohort study with outcome-dependent weighting, and analyzed through the inverse probability weight estimator framework (Cai and Zheng, 2011). Both MVC and FUC can be applied similarly to the weighted partial likelihood as in the case-cohort design.…”
Section: Calibration Approachesmentioning
confidence: 99%
“…A nested case-control study can be viewed as a cohort study with outcome-dependent weighting, and analyzed through the inverse probability weight estimator framework (Cai and Zheng, 2011). Both MVC and FUC can be applied similarly to the weighted partial likelihood as in the case-cohort design.…”
Section: Calibration Approachesmentioning
confidence: 99%
“…Cases were matched with four controls, on sex, year of birth, drug administration route and duration of drug use. Previous research has shown that matching more than four controls with each case does not significantly add statistical power to the analysis (Cai & Zheng, 2012;Ury, 1975). Controls were never matched to more than one case and deceased users were excluded from the RELIS database in order to avoid that they were matched with cases.…”
Section: Case Definition Study Design and Participantsmentioning
confidence: 99%
“…The small cohort was used to derive a Cox proportional hazard model which was then applied to the full dataset. The sampling method used in case-control selection from larger cohorts can significantly affect the results of any analysis 21 . Use of a single pass assessment of the model will give a false impression of the performance: a non-parametric boot-strapping technique as described for other screening populations where multiple data sets are hard to acquire should have been used to improve assessment, in particular to identify confidence intervals for the effectiveness of the test 22 .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%